SIA "Gjensidige Baltic" darbības analīze - Ivbule, Aiga (Latvijas Universitāte, 2011)
Bakalaura darba tēma ir „AAS Gjensidige Baltic darbības analīze”. Precizējums darba tēmai - no uzņēmuma darbības analīzes tieši finanšu analīze. Bakalaura darbs ir izstrādāts ar mērķi iepazīties ar AAS Gjensidige Baltic vispārīgo informāciju, finanšu pārskata sastāvdaļām finanšu analīzes jēdzienu un analizēt apdrošināšanas sabiedrības finanses piecu gadu ietvaros ar rentabilitātes rādītāju, likviditātes rādītāju, aktivitātes analīzes un kapitāla struktūras analīzes palīdzību. Darbs sastāv no ievada, trīs nodaļām, septiņpadsmit apakšnodaļām, secinājumiem un priekšlikumiem. Galvenais secinājums – AAS Gjensidige Baltic ir mērķtiecīga apdrošināšanas sabiedrība, kas tiecas uz izaugsmi un stabilitāti, par to liecina rādītāju vienlīdzība un atbilstība normām

The topic of the bachelor’s paper is „ The Analysis of LTD Gjensidige Baltic Operation”. Clarification of the topic – just financial analysis has been worked out of the whole operation analysis. The aim of the bachelor’s paper is to analyse the financial operations of AAS Gjensidige Baltic. The main tasks are to acquaint myself with the general information about AAS Gjensidige Baltic and the concept of the financial analysis, to analyse the finance of the insurance company with the help of a cost-efficiency ratio, liquidity parameter, activity analysis, capital structure analysis and the specific factors of the insurance company. The paper consists of an introduction, 3 chapters, 17 sub-sections, conclusions and suggestions. The main conclusion – AAS Gjensidige Baltic is a targeted insurance company, which is favorable to growth and stability as it is indicated by equality of the parameters and compliance with standarts.
The Analysis of LTD Gjensidige Baltic Operation
Keywords: Ekonomika